Novel Minimal Access Bone Anchored Hearing Implant Surgery and a New Surface Modified Titanium Implant, the Birmingham Experience. Issue 10 (December 2019) - Limbrick, Jack; Muzaffar, Jameel; Kumar, Raghu; Mulvihill, Daniel; Gaskell, Peter; Addison, Owen; Monksfield, Peter; Banga, Rupan
Abstract : Background: Bone anchored hearing implants (BAHI) are widely used and highly successful, accompanied with a high level of patient satisfaction across most techniques. A large UK teaching hospital switched from the previously used wide diameter titanium fixture and drilling system to the novel minimally invasive technique and laser ablated titanium implant. Before this change the rates of fixture failure and skin problems necessitating abutment change were 1% each. Methods: Retrospective case note review of consecutive BAHI patients drawn from an electronic database between January 2015 and October 2016. Results: Data from a total of 118 procedures were reviewed, with different combinations of surgical techniques and implant types. Sixty procedures were performed via the novel minimally invasive technique with 21 failures (35%). Fourty-eight modified minimally invasive technique procedures were performed with seven failures. In 64 of the procedures, laser ablated titanium fixtures were placed with 21 failures (32.8%). In 54 procedures wide diameter titanium fixtures were placed with eight failures (5%). Conclusion: Initial experience with the novel minimally invasive technique and laser ablated titanium fixture showed significantly higher failure rates than expected. This prompted a change to an open technique and subsequent abandonment of the laser ablated titanium fixture and custom drilling solution in our institution.